1993
DOI: 10.1103/physrevb.47.8996
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated hopping of a single Abrikosov vortex

Abstract: Thermally activated hopping of a single Abrikosov vortex has been investigated for a thin Pb film that was decorated with an artificial pinning structure. To determine the location of the vortex, the Pb film is fabricated to be one electrode of a cross-strip superconductor/normal-metal/insulator/superconductor (SNIS ) Josephson junction. Distortions in the Fraunhofer pattern specify the vortex location. As the temperature is raised toward T" the vortex depins from the artificial pinning site and reproducibly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…4,5 In addition, it was established that an intrinsically pinned vortex will spontaneously start to move around when the superconducting order parameter ⌬ is suppressed to about 20% of the Tϭ0 value ⌬ 0 . 1,6,7 In all of this work, there was no control of the locations where the vortex would move.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, it was established that an intrinsically pinned vortex will spontaneously start to move around when the superconducting order parameter ⌬ is suppressed to about 20% of the Tϭ0 value ⌬ 0 . 1,6,7 In all of this work, there was no control of the locations where the vortex would move.…”
Section: Introductionmentioning
confidence: 99%
“…(3), Eq. (5). Afterwards, we shall use it to describe the flux exchange and flux relaxation over the entire superconductor.…”
Section: Generalization Of Flux Exchange and Flux Relaxationmentioning
confidence: 99%
“…Qiang Li [28] made used of a Pb-Al-Also,-PbBi junction in order to further investigate the motion of a single vortex and measure the elementary pinning force in these SNIS junctions. Subsequently, Sanders [29] studied the thermal depinning process in a Pb-Al-Al,O,-PbBi junction and found that the first depinning occurs when the order parameter of the bulk Pb is about 20% of the T = 0 value. Junghyun Sok [30] repeated this experiment for a Nb-Al-Al,O,-Nb junction and found that the corresponding quantity was equal to 24%.…”
Section: List Of Tablesmentioning
confidence: 99%